TRAJECTORIES OF INDIANITY: THEOLOGY AND POLITICS - Beaucage, Pierre (Revista de Historia Social y de las Mentalidades, 2011)
In this paper, I want to esplicit the process thro ugh which the representation of indianity  was historically constructed in Western imaginary,  and stress the interrelation between the  religious and political dimensions. The first defin ition was theological and it remained polarized  between the « innocent native » and the « savage sl ave of the Devil ». Las Casas’ vision, put  aside during long periods in view of the difficulti es of evangelization, was recently rescued by  Theology of Liberation and one of its avatars, Indi an Theology; a lay version was eleborated by  the ecologist movement. The political representatio n of the Indian, in the Spanish colonies of  Mesoamerica and the Andes, was rooted in Aristotle’ s conception of men « born to obey », which  corresponded to a practice of  subordination . To the North and the South of the continent  (excepting the interlude of French commercial  articulation ), a policy of  substitution was  accompanied by an image of the Indian as doomed to  disappear from a land « manifestly destined  » to European settlers. Present-day indigenous orga nizations develop a self-representation which  combines lascasian-ecologist elements about their p recolonial past with the modern concept of  nation and its corollaries, territory and self-dete rmination.
Keywords: Indianity; Theological trayectory; Political trayectory.